SPEECH STYLE USED IN TEACHING ENGLISH THROUGH WHATSAPP DURING PANDEMIC OF COVID-19 - Khoiriyah, Uswatun (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
Speech style is a unique characteristic of an individual. Specifically, to accomplish the learning purpose a teacher is needed to use speech style to assist their students. There was different speech style between male and female English teachers while explaining the subject. Moreover, in the pandemic Covid-19 condition there is a requirement to use technology information as learning media such as Whatsapp. The research objectives are (1) to analyze the type of speech styles that the teacher used in teaching English through WhatsApp during pandemic of Covid-19 at SMP Islam Al Azhaar Tulungagung (2) to analyze the students’ perception of speech style used by the teacher through WhatsApp during pandemic of Covid-19 at SMP Islam Al Azhaar Tulungagung. The method of research is qualitative descriptive by using primary source as voice note, questionnaire to collect the data and data was analysis using Baxter’s speech styles categorization. The result show that (1) the male english teacher often used matter of fact features because he wanted to be more factual and referential when he explained the material to the students. Then, the most dominant of the female teachers speech style was co-operative. The female english teachers often used co operative features because she wanted to have good cooperation with their students in tlearning English. (2) The students said that they more motivated learning English when their teacher appreciate them in addition the most of students hoped that teacher should asked used referential question because it can increase their ability in English.